Singular vectors of orthogonally decomposable tensors - Robeva, E; Seigal, A (Taylor and Francis, 2017)
Orthogonal decomposition of tensors is a generalization of the singular value decomposition of matrices. In this paper, we study the spectral theory of orthogonally decomposable tensors. For such a tensor, we give a description of its singular vector tuples as a variety in a product of projective spaces.